(untitled) (Journal of the College of Basic Education, 2022)
The current study aimed to identify the impact of the conflicting events strategy on the art education department’s achievement in the theories of artistic creativity. The research in which the researcher followed the experimental method for two research groups (experimental and control) and the research community consisted of students of the Department of Art Education - College of Basic Education - Al-Mustansiriyah University - Fourth Stage - totaling 185 students. My achievement accordingly to measure the achievement of the students of the two research groups, which was characterized by honesty and stability, and the researcher used the statistical bag (Spss) as the ratio and the current study, as it was shown that the students of the experimental group events over the control group who studied in the traditional method.